2021
DOI: 10.1177/14407833211057310
|View full text |Cite
|
Sign up to set email alerts
|

The victims, villains and heroes of ‘panic buying’: News media attribution of responsibility for COVID-19 stockpiling

Abstract: Societies often respond to a crisis by attributing blame to some groups while constructing others as victims and heroes. While it has received scant sociological attention, ‘panic buying’ is a critical indicator of such public sentiment at the onset of a crisis, and thus a crucial site for analysis. This article traces dynamics of blame in news media representations of an extreme period of panic buying during COVID-19 in Australia. Analysis reveals that lower socio-economic and ethnically diverse consumers wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Media articles routinely returned to the tower residents' ethnic backgrounds, creating a perception of cultural inferiority and poor choices that not only affirm racialised ideologies, but obscure the lack of adequate support and investment for public housing infrastructure. Similar dynamics were witnessed in the media coverage of COVID-related supply chain issues, which disproportionately blamed ethnically diverse and low socio-economic communities for 'panic buying', while veiling the structural reasons behind the stock shortages (Phillips et al, 2021). Furthermore, cultural traits assigned to the nationalities and ethnicities of tower residents -such as communitarian living and the heightened importance of extended families -were deemed to render them more vulnerable to the virus and to spreading infection:…”
Section: Spatial and Cultural Vulnerabilitymentioning
confidence: 84%
“…Media articles routinely returned to the tower residents' ethnic backgrounds, creating a perception of cultural inferiority and poor choices that not only affirm racialised ideologies, but obscure the lack of adequate support and investment for public housing infrastructure. Similar dynamics were witnessed in the media coverage of COVID-related supply chain issues, which disproportionately blamed ethnically diverse and low socio-economic communities for 'panic buying', while veiling the structural reasons behind the stock shortages (Phillips et al, 2021). Furthermore, cultural traits assigned to the nationalities and ethnicities of tower residents -such as communitarian living and the heightened importance of extended families -were deemed to render them more vulnerable to the virus and to spreading infection:…”
Section: Spatial and Cultural Vulnerabilitymentioning
confidence: 84%
“…A study in Australia examining news media coverage of panic buying during COVID-19 indicates that lower socio-economic and ethnically diverse consumers were blamed disproportionately. This was evident through dehumanising language, with those engaging in panic-buying described as selfish and shameful (Phillips et al, 2021).…”
Section: Media Dynamics Of Blame During Public Health Crisesmentioning
confidence: 99%
“…While there is emergent research evidence on the attribution of blame during the early phase of the pandemic, in particular the initial outbreak (Lövenmark et al, 2023; Ogbodo et al, 2020; Phillips et al, 2021; Rooke, 2021), and the dynamics of blame attribution on social media (Choli and Kuss, 2021; Nguyen et al, 2021), limited attention has been paid to understanding blame in subsequent waves of the virus and as countries attempted to respond to the pandemic. Our study, therefore, seeks to consider the figures of blame beyond the early phase of the pandemic, which as established is often characterised by externalising blame, to consider subsequent waves of the virus and the UK’s response to the crisis.…”
Section: Media Dynamics Of Blame During Public Health Crisesmentioning
confidence: 99%
“…Studies of infectious disease outbreaks have observed that these are often accompanied by narratives of heroes, victims and villains. Such narratives make sense of uncertainty and provide templates for action, offering the promise of individual control amid chaos (Atlani-Duault et al 2020;Bory et al 2023;Pearce 1973;Phillips et al 2021;Roy et al 2019;Wagner-Egger et al 2011;Xiao et al 2021). In allocating blame to individuals, such narratives also draw attention away from structural and governance factors shaping the distribution of wellness and illness in society (Matthewman and Huppatz 2020), and disproportionately construct less privileged and marginal members of society-sexual and ethnic minorities, immigrants and other outsiders, and the poor-as the villains in accounts of disease spread (Phillips et al 2021;Team and Manderson 2020;Wynn 2021).…”
mentioning
confidence: 99%
“…Such narratives make sense of uncertainty and provide templates for action, offering the promise of individual control amid chaos (Atlani-Duault et al 2020;Bory et al 2023;Pearce 1973;Phillips et al 2021;Roy et al 2019;Wagner-Egger et al 2011;Xiao et al 2021). In allocating blame to individuals, such narratives also draw attention away from structural and governance factors shaping the distribution of wellness and illness in society (Matthewman and Huppatz 2020), and disproportionately construct less privileged and marginal members of society-sexual and ethnic minorities, immigrants and other outsiders, and the poor-as the villains in accounts of disease spread (Phillips et al 2021;Team and Manderson 2020;Wynn 2021). In this study of COVID-19 in two countries with very small case numbers, narratives of blame took on particular characteristics: not only did they construct villains, they also mapped and diagrammed their movements in media spectacles of villainised behaviour.…”
mentioning
confidence: 99%